Simultaneous Hydatid Cyst of the Liver and Left Iliac Fossa: An Unusual Case Report. (3rd September 2019) - Bhandari, Tika Ram; Shahi, Sudha
Abstract : Hydatid disease is a significant health problem in many livestock-rearing areas especially in the developing world, mainly caused by Echinococcus granulosus . The liver and lung are the most common affected sites. However, hydatid disease can occur anywhere in the body. Simultaneous involvement of two organs or sites is very unusual, mainly for organs other than the lung and liver. We thus report a very unusual combination of hepatic and left iliac fossa with hydatid disease in an adult patient. A 37-year-old farmer from a village presented with intermittent right upper quadrant and left iliac fossa pain associated with distention of abdomen for one month. Abdominal radiological investigations reported hydatid cyst disease; one cyst was found in the right lobe of the liver and another in the left iliac fossa. Positive IgG antibody by the ELISA test also confirmed the diagnosis. Pericystectomy and excision of hydatid cyst without spillage of content for the liver and left iliac fossa were done, respectively. Patient was discharged on the 10th postoperative day with an uneventful postoperative course. There was no recurrence of the lesion during one-year follow-up period. A combination of hydatid disease in the liver and iliac fossa is very unusual, so clinician should have thoughts regarding this rare entity as an important differential diagnosis.